Characterisation of the physico-chemical and solid-state behaviour of drugs in HFA-134 and 227 - Bouhroum, Abdennour (2011)
Most drugs have a considerably low solubility in the environmentally friendly hydrofluoroalkane propellants (HFAs) currently used in pressurized metered dose inhalers (pMDIs). As a consequence, instability can occur from crystal growth and Ostwald ripening of the system altering the therapeutic performance of the pMDI. Understanding and being able to predict the behaviour of such drugs in the propellant will help in selecting the correct co-solvents and/or surfactants to increase the stability of such formulations. When anhydrous beclomethasone dipropionate (BDP) is suspended in tricholoromonofluoromethane (CFC-11) rapid crystal growth occurs, leading to the formation of a clathrate. Since chlorofluorocarbon (CFCs) propellants have been replaced by HFAs, many questions arose concerning the ability of BDP to form clathrates in the HFA and any stability issues that arise from such reformulation. Clathrates are crystalline compounds consisting of a lattice of one type of molecule that hosts a second type of “guest” molecule within its structure. Since the solid state chemistry can significantly alter the physical interactions within a suspension formulation, it is crucial to determine the most stable crystalline form in the presence of the propellant.